Determining the Compressive, Flexural and Splitting Tensile Strength of Silica Fume Reinforced Lightweight Foamed Concrete - Mydin, M.A.O.; Md. Sani, N.; Mohd Yusoff, M.A.; Ganesan, S. (EDP Sciences, 2014)
This study investigated the performance of the properties of foamed concrete in replacing volumes of cement of 10%, 15% and 20% by weight. A control unit of foamed concrete mixture made with ordinary Portland cement (OPC) and 10%, 15% and 20% silica fume was prepared. Three mechanical property parameters were studied such as compressive strength, flexural strength and splitting tensile of foamed concrete with different percentages of silica fume. Silica fume is commonly used to increase the mechanical properties of concrete materials and it is also chosen due to certain economic reasons. The foamed concrete used in this study was cured at a relative humidity of 70% and a temperature of ±28°C. The improvement of mechanical properties was due to a significant densification in the microstructure of the cement paste matrix in the presence of silica fume hybrid supplementary binder as observed from micrographs obtained in the study. The overall results showed that there is a potential to utilize silica fume in foamed concrete, as there was a noticeable enhancement of thermal and mechanical properties with the addition of silica fume.